Mesoscopic self-organization of a self-assembled supramolecular rectangle on highly oriented pyrolytic graphite and Au(111) surfaces - Gong, Jian-Ru (National Academy of Sciences, 2005)
A self-assembled supramolecular metallacyclic rectangle was investigated with scanning tunneling microscopy on highly oriented pyrolytic graphite and Au(111) surfaces. The rectangles spontaneously adsorb on both surfaces and self-organize into well ordered adlayers. On highly oriented pyrolytic graphite, the long edge of the rectangle stands on the surface, forming a 2D molecular network. In contrast, the face of the rectangle lays flat on the Au(111) surface, forming linear chains. The structures and intramolecular features obtained through high-resolution scanning tunneling microscopy imaging are discussed.